Keberhasilan Persilangan Tomat Varietas Komersial (Lycopersicum esculentum L.) dengan Tomat Mutan Tahan Simpan - Gungun Wiguna; Elfira Rosalita; Anas Anas; Neni Rostini; Syariful Mubarok; Hiroshi Ezura (Zuriat, 2019)
Post-harvest loss is an obstacle for tomato farmers that cause tomato farming being unprofitable. Utilization of mutant genes prolong tomato fruit shelf life through crossing is one of the best solutions to improve the fruit quality. The objective of this study was to determine the success of cross-pollination between commercial tomato varieties and shelf life of mutant tomatoes. Two mutant tomato lines Sletr1-1 and Sletr1-2, and one wild type strain were crossed with four commercial varieties (Intan, Mutiara, Ratna, and Mirah ). The results showed that the success rate of crossing ranged from 77.50% to 100%, with an average of 95.76%. The average maximum growth potential of seeds produced was 89.17% with the lowest value of 75% and the highest 98.5%. The most top success of crosses was built by a combination of crossing Ratna x Sletr1-2, and the combination of Mirah x Sletr1-1 showed the lowest percentage of the crossing. The Intan showed the highest success as female parent of crossing, while Mirah was the lowest production of the crossing. The plant height of all hybrid was smaller compared to the commercial varieties.